How can we do it right? : ethical uncertainty in Swedish Sami research - Drugge, Anna-Lill (Journal of Academic Ethics, 2016)
Research related to indigenous peoples in Sweden and elsewhere has a history marked by discriminatory practice and unequal research processes. Sweden has still not been very visible in terms of openly debating, developing and implementing ethical strategies specifically suited for indigenous research. The present study explores how research ethics is discussed among scholars within the Sami research field in contemporary Sweden. Fifty-six research proposals deriving from eight different research institutions and 160 individual researchers are analyzed, discovering how scholars relate to research ethics when planning for new research projects related to the indigenous Sami. The results demonstrate that ethical guidelines for research are often referred to, but that a common view on what guidelines to use is lacking, leading to a notable variety between different researchers. Ethical discussions are present in the vast majority of the proposals, however there are notable differences between the theories around how to proceed in a culturally safe, ethical manner, and the proposed methods that are to be used to implement theory in practice. In conclusion, there exists a great uncertainty among scholars on where to seek ethical guidance, how to relate to current legislation around research ethics and at the same time act ethically in a culturally appropriate manner. This uncertainty leads to questioning whether discussions of ethics are relevant in the first place, what they are supposed to include, how they are meant to be undertaken and what consequences can be expected from the presence or absence of ethics in indigenous research.